REPRESENTATION OF RURAL AND URBAN DICHOTOMY IN KAMALA MARKANDAYA’S WORKS (International Journal of Food and Nutritional Sciences, 2023)
The rural and urban dichotomy is a recurring theme in Kamala Markandaya’s works, reflecting the tension between traditional rural life and the modernity of urban existence. Through her portrayal of characters caught between these contrasting worlds, Markandaya explores the social, cultural, and psychological impacts of this shift. This paper examines how Markandaya uses the rural and urban settings to symbolize broader themes of change, identity, and conflict in post-colonial India. In particular, her novels such as Nectar in a Sieve and A Handful of Rice portray rural life as both idyllic and oppressive, while urban spaces are depicted as spaces of opportunity and alienation. The study focuses on the ways Markandaya’s characters navigate these spaces, often highlighting the internal and external struggles they face while adapting to or resisting change. The research explores how the author critiques the socio-economic pressures of modernization and urbanization, offering a nuanced reflection on the consequences of India's transition from a rural-based economy to an industrialized society. Ultimately, this paper underscores Markandaya's critical examination of rural-urban divisions and the resultant impact on individual lives and communities.